Gaya Bahasa Al-Tawkid daripada Perspektif Nahu dan Balaghah Arab - Bambang Muhamad Rafadi Yusoff; Saini Ag. Damit (2016)
This article expounds narratively the description of al-Tawkid element and its role in Arabic language and prime literature. Discussion concerning al-Tawkid is not only limited to the debate in Arabic grammatical knowledge; it also crosses the Arabian socioculture itself which is manifested through rhetorical authority (balaghah) and its literature (adab). The function and implication of al-Tawkid in Arabic language and culture have placed the language style (uslub) in a class of its own. The outcome of discussion in this article found that Arabic language and culture do not only describe al-Tawkid in daily discourse, but it also undertakes the aura of intellectuality and personal perseverance of the Arab nation in the stage of sustainable physics and linguistics. Look at how they express assertiveness in perceiving a certain thing which becomes an ambition or a thrust in everyday life; not only through grammar al-Tawkid al-Lafziyy or al-Ma'nawiyy alone, yet it extends over other grammatical elements such as al-Qasm (oath), al-Maf‘ul al-Mutlaq (extreme accusative), zarf al-Zaman (Position of Time), al-Nida' (summon), al-Badal (Substitution), al-Na'at (adjective) and so forth. Similarly, when searching through a treasure of literature in which stores various lines and strains of very fascinating and impressive Arabic prime literature; one of them involves the use of language style al-Tawkid in literary expressions by Arabian writers, such as al-Mubulaghah (Hyperbole), al-Itnab (Elaboration), al-Taqdim wa al-Ta’khir and et cetera. Hence, it is not surprising that al-Quran al-Karim is rich with messages concerning assertion and reinforcement of the verses of Allah SWT that uses language style al-Tawkid of the version of Arabic language and culture which lifts its prestige at once to the most honorable position in the world and hereafter.